PENGGUNAAN PERMAINAN PEPETIK BERBANTUAN ANALISIS ADIKSIMBA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA DALAM MENENTUKAN PIKIRAN POKOK - Maulani, Mita; Sunarya, Dede Tatang; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2017)
Lack of student motivation to follow the learning and use of methods used by teachers in learning to determine the main thoughts less attractive for students, causing less motivated students to follow the learning well. Therefore, the use of game Pepetic-assisted analysis Adiksimba to improve the value of the process and student learning outcomes. The use of Pepetic game is used to improve the result of lesson plan, implementation or learning process, student activity, and result of student learning test in cognitive aspect and psychomotor aspect. The method used in this research is PTK with Kemmis model design and Mc Taggart. After using Adiksimba-assisted Pepetic analysis game, the learning cycle I learned 84.8%, 83% learning, 59% student activity, and student learning test result in the subject matter determined 75% of complete students. While in cycle III, the results of planning and implementation of teacher performance learning reaches 100%, student activity reaches 90.3%, and learning test results reach 88.5%.Â